The U-shaped association of non-high-density lipoprotein cholesterol with all-cause and cardiovascular mortality in general adult population - Huang, Yu; Yan, Meng Qi; Zhou, Dan; Chen, Chao Lei; Feng, Ying Qing (Frontiers in Cardiovascular Medicine, 2023)
Background: Non-high-density lipoprotein cholesterol (non-HDL-C) has been associated with atherosclerosis. However, the association between non-HDL-C and mortality in adult population remains unclear. We intended to investigate the association of non-HDL-C with cardiovascular and all-cause mortality using national representative data. Methods: The study included 32,405 participants from the National Health and Nutrition Examination Survey (1999-2014). Mortality outcomes were ascertained by linkage to National Death Index records through December 31, 2015. Multivariable-adjusted Cox regression models were used to evaluate hazard ratio (HR) and 95% confidence interval (CI) of non-HDL-C concentrations in quintiles. Two-piecewise linear regression and restricted cubic spline analyses were performed to test dose-response associations. Results: After a median follow-up of 98.40 months, 2859 (8.82%) all-cause and 551 (1.70%) cardiovascular deaths occurred. Compared with the highest group, the multivariable-adjusted hazard ratio (HR) of the first quintile for all-cause mortality was 1.53 (95%CI, 1.35-1.74). Higher non-HDL-C above a cutoff value of 4.9 mmol/L was related with cardiovascular mortality (HR=1.33, 95%CI, 1.13–1.57). A U-shaped relationship between non-HDL-C and all-cause mortality was found in spline analysis with a cutoff value around 4 mmol/L. Similar results in subgroups analyses were found among male, non-white population, participants who were not taking lipid-lowering drugs, and with body mass index (BMI) <25 kg/m2. Conclusion: Our findings suggest a U-shaped association between non-HDL-C and mortality among adult population.